Comparison of interradicular distances and cortical bone thickness in Thai patients with class I and class II skeletal patterns using cone-beam computed tomography - Nattida Khumsarn (2018)
© 2016 by Korean Academy of Oral and Maxillofacial Radiology. Purpose: This study evaluated and compared interradicular distances and cortical bone thickness in Thai patients with Class I and Class II skeletal patterns, using cone-beam computed tomography (CBCT). Materials and Methods: Pretreatment CBCT images of 24 Thai orthodontic patients with Class I and Class II skeletal patterns were included in the study. Three measurements were chosen for investigation: the mesiodistal distance between the roots, the width of the buccolingual alveolar process, and buccal cortical bone thickness. All distances were recorded at five different levels from the cementoenamel junction (CEJ). Descriptive statistical analysis and t-tests were performed, with the significance level for all tests set at p<0.05. Results: Patients with a Class II skeletal pattern showed significantly greater maxillary mesiodistal distances (between the first and second premolars) and widths of the buccolingual alveolar process (between the first and second molars) than Class I skeletal pattern patients at 10 mm above the CEJ. The maxillary buccal cortical bone thicknesses between the second premolar and first molar at 8 mm above the CEJ in Class II patients were likewise significantly greater than in Class I patients. Patients with a Class I skeletal pattern showed significantly wider mandibular buccolingual alveolar processes than did Class II patients (between the first and second molars) at 4, 6, and 8 mm below the CEJ. Conclusion: In both the maxilla and mandible, the mesiodistal distances, the width of the buccolingual alveolar process, and buccal cortical bone thickness tended to increase from the CEJ to the apex in both Class I and Class II skeletal patterns.